Unraveling the Metabolic Requirements of the Gut Commensal Bacteroides ovatus - Fultz, Robert; Ticer, Taylor; Ihekweazu, Faith D.; Horvath, Thomas D.; Haidacher, Sigmund J.; Hoch, Kathleen M.; Bajaj, Meghna; Spinler, Jennifer K.; Haag, Anthony M.; Buffington, Shelly A.; Engevik, Melinda A. (Frontiers in Microbiology, 2021)
Background: Bacteroidetes are the most common bacterial phylum in the mammalian intestine and the effects of several Bacteroides spp. on multiple facets of host physiology have been previously described. Of the Bacteroides spp., Bacteroides ovatus has recently garnered attention due to its beneficial effects in the context of intestinal inflammation. In this study, we aimed to examine model host intestinal physiological conditions and dietary modifications in order to characterize their effects on B. ovatus growth. Methods & Results: Using Biolog phenotypic microarrays, we evaluated multiple primary carbon sources and determined that B. ovatus can use 10 disaccharides, 4 trisaccharides, 4 polysaccharides, 4 polymers, 3 L-linked sugars, 6 D-linked sugars, 5 amino-sugars, 6 alcohol sugars and 15 organic acids as primary carbon sources. To further understand carbohydrate metabolism by B. ovatus, the presence of glycosyl hydrolase (GH) genes were evaluated in 6 annotated B. ovatus genomes. This analysis revealed a large repertoire of GH genes in B. ovatus, including high expression of GH 3, GH 28, GH 31, GH 43, GH 76, GH 78, GH 86, GH 88, and GH 92. Furthermore, proteomic profiling of B. ovatus revealed that a significant portion of the B. ovatus proteome was involved in metabolic pathways. In the proteome, we identified multiple proteins with antioxidant properties and reasoned that these proteins may support B. ovatus growth in the physiological conditions of the intestinal environment. We found that B. ovatus grew robustly in various pH, osmolarity, bile, ethanol, and H2O2 concentrations; indicating that B. ovatus is a well-adapted gut microbe. Conclusions: Taken together, we have demonstrated that key host and diet-derived changes in the intestinal environment influence B. ovatus growth. These data provide the framework for future work toward understanding how diet and lifestyle interventions may promote a beneficial environment for B. ovatus growth.